THE COMPARISON ANALYSIS INCOME BETWEEN THE RICE FARMING BUSINESS WITH RICE FARMING BY THE CHANGE PRODUCT WITH FISH FARMING (SISTEM SELANG) IN PAGARANTONGA VILLAGE, PANYABUNGAN SUBSDISTRICT, MANDAILING NATAL DISTRICT, NORTH SUMATRA PROVINCE - Zulfahmi '; Eni Yulinda; Darwis ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Study was conducted in January 2016 at Pagarantonga village PanyabunganSubsdistrict, Mandailing Natal District, North Sumatra Province. The study wasaimed to analyze comparison costs, production and earnings between farm systemand rice farming by change product with fish farming (sistem selang) inPagarantonga village. Method used in research was survey with respondents about27 people were selected purposively sampling. Production costs incurred businessrice farming by change product with fish farming (sistem selang) higher than 143% farming rice in a year. The number of rice production in farming rice more 57.7% than the number of rice production business rice farming by change productwith fish farming (sistem selang) a year. Gross income and net income obtainedby farmers business rice farming by change product with fish farming ( sistemselang) higher 79 % and than 24.6 % farming rice in a year. Contribution giventhe business of fish farming to the total net income farmers rice farming bychange the product with fish farming (sisem selang) of 52.4 % .Keywords: costs, production, income, rice farming by change product with fishfarming (sistem selang)